Perkembangan Peserta Didik di Era Artificial Intelligence: Peran Deep Learning dalam Mewujudkan Pembelajaran Adaptif dan Persona - Luvita Indah Pratiwi; Miftahul Hanifa; Nencya Safara; Chelsa Bunga Nagita; Salsabilla Dinar Sandhi (Universitas PGRI Madiun, 2026)
This study aims to analyze the role of Deep Learning in supporting student development through adaptive and personalized learning in the era of Artificial Intelligence (AI). A qualitative library research approach was employed using scientific articles, books, and relevant documents. Data were analyzed through content analysis. The findings indicate that Deep Learning can personalize learning materials, strategies, and assessments according to students' characteristics, thereby improving learning effectiveness. However, its implementation still faces challenges related to teachers' readiness, technological infrastructure, and ethical issues. Therefore, the use of AI should be supported by collaboration among technology, educators, and educational policies.